Rancang Bangun Aplikasi Laporan Penjualan Berbasis Web Menggunakan Metode Prototype - Alif Dion Pratama; Fahmi Aziz; Muhamad Afriansyah (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
The development of information and communication technology has had a significant impact on various aspects of life, including in the business world. To support operational efficiency and effectiveness, companies are increasingly turning to the use of web-based applications to manage various business processes, including sales reporting. This research aims to design and build a web-based sales report application for Taktik Coffee, a growing local coffee company. The development method used in this research is the prototype method, which allows users and developers to interact iteratively in the application development process. The sales report application designed and developed in this research has key features such as monthly sales recording, sales analysis based on specific time periods and data visualization in the form of graphs. This application is also equipped with user management features and access rights based on roles. The result of this research is a web-based sales report application that can help Taktik Coffee in managing and analyzing their sales efficiently. It is expected that this application can improve better decision making based on accurate and structured sales data